Molecular modeling on the identification of potential Janus Kinase 3 (JAK3) inhibitor based on the Indonesian Medicinal Plant Database - Muhammad Arba; Sanang Nur Safitri; Andry Nur Hidayat; Arry Yanuar; Muhammad Sulaiman Zubair; Asmiyenti Djaliasrin Djalil; Daryono Hadi Tjahjono (Institute for Research and Community Services (LPPM) ITB, 2020)
The Janus tyrosine kinases (JAKs) have shown great promise as therapeutic protein targets in the treatment of cancer and inflammation diseases. This study used pharmacophore modeling to identify potential inhibitors of Janus kinase 3 (JAK3). A pharmacophore model was developed based on a known JAK3 inhibitor (1NX) and was employed to search for potential JAK3 inhibitors against Indonesian herbal compounds. Among 28 hit molecules that were identified and subjected to a molecular docking protocol against JAK3, the three compounds that had the highest affinities toward JAK3 were camelliaside B, 3-O-galloylepicatechin-(4beta-6)-epicatechin-3-O-gallate, and mesuaferrone B. These were then each subjected to a 50-ns molecular dynamics (MD) simulation. Analysis of RMSD and RMSF values indicated that the three compounds reached stability during the MD simulation. Interestingly, all three compounds had lower binding energies than 1NX against JAK3, as predicted by the MM-PBSA binding energy calculation.